Clinical event reductions in high-risk patients after renal denervation projected from the global SYMPLICITY registry - Schmieder, Roland; Mahfoud, Felix; Mancia, Giuseppe; Narkiewicz, Krzysztof; Ruilope, Luis; Hutton, David; Cao, Khoa; Hettrick, Douglas A.; Fahy, Martin; Schlaich, Markus P.; Bohm, Michael; Pietzsch, Jan B. (European Heart Journal - Quality of Care and Clinical Outcomes, 2022)
Aims Renal denervation has been shown to lower blood pressure in sham-controlled trials and represents a device-based treatment option for hypertension. We sought to project clinical event reductions after radiofrequency renal denervation using a novel modelling approach. Methods and results The Global SYMPLICITY Registry is a global, prospective all-comer registry to evaluate safety and efficacy after renal denervation. For this analysis, change in office systolic blood pressure from baseline was calculated from reported follow-up in the Global SYMPLICITY Registry. Relative risks for death and other cardiovascular events as well as numbers needed to treat for event avoidance were obtained for the respective blood pressure reductions based on previously reported meta-regression analyses for the full cohort and high-risk subgroups including type 2 diabetes, chronic kidney disease, resistant hypertension, and high basal cardiovascular risk. Average baseline office systolic blood pressure and reduction estimates for the full cohort (N = 2651) were 166 +/- 25 and -14.8 +/- 0.4 mmHg, respectively. Mean reductions in blood pressure ranged from -11.0–21.8 mmHg for the studied high-risk subgroups. Projected relative risks ranged from 0.57 for stroke in the resistant hypertension cohort to 0.92 for death in the diabetes cohort. Significant absolute reductions in major adverse cardiovascular events over 3 years compared with the projected control (8.6 +/- 0.7% observed vs. 11.7 +/- 0.9% for projected control; P < 0.01) were primarily due to reduced stroke incidence. The robustness of findings was confirmed in sensitivity and scenario analyses. Conclusion Model-based projections suggest radiofrequency renal denervation for patients with uncontrolled hypertension adds considerable clinical benefit across a spectrum of different cohort characteristics.
CRIS-Team WoS Importer:2022-10-21